Pernikahan Satu Marga: Adat Istiadat di Desa Simangambat dalam Perspektif Hadis - Indah Maulida (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This study examines the prohibition of same-clan marriage among the Mandailing community in Simangambat Village, North Padang Lawas. Traditionally, marrying within the same clan is forbidden, as clans are believed to share bloodlines, making such unions taboo and akin to incest. This custom aims to maintain social harmony but lacks a basis in Islamic law. Islam prohibits marriage only between mahram (close blood relatives), and same-clan marriages are not explicitly forbidden if the individuals are not mahram. Using qualitative methods, including interviews and observations with community and religious leaders, the study found that while many still uphold the tradition, awareness is growing that it conflicts with Islamic teachings. Some religious leaders emphasize prioritizing Islamic law over local customs. The research concludes that the prohibition is cultural rather than religious and that increasing awareness is leading the community to reconsider the tradition, emphasizing the need to align local customs with Islamic principles in marriage decisions.